International finance : theory et policy / Paul R Krugman; Maurice Obstfeld; Marc J Melitz - Krugman, Paul R.
International Finance: Theory and Policy provides engaging, balanced coverage of the key concepts and practical applications of the discipline. An intuitive introduction to international finance theory is followed by detailed coverage of policy applications. With this new 11th Edition, Global Edition, the author team of Nobel Prize-winning economist Paul Krugman, renowned researcher Maurice Obstfeld, and Marc Melitz of Harvard University continues to set the standard for international finance courses.